The Contemplation Stage of Smoking Behavior Change among Health Students in Kupang City - Elisabeth Ina Talapessy; Petrus Romeo; Enjelita Mariance Ndoen (Universitas Nusa Cendana, 2021)
A health department student is an individual who has a higher level of knowledge and education in the field of health. However, around 37,3% of college students in Indonesia, including health students, are smokers. Previous studies of health students showed the desire of smokers to quit smoking. The intention to quit smoking can be identified through a process of change at the contemplation stage. The research described smoking behaviour change on the contemplation stage on health department students in Kota Kupang in 2021. The type of research was qualitative with the technique of in-depth interviews. This research recruited nine health students in Kota Kupang who have willing to change their smoking behaviour. The research found that while all informants intend to quit smoking, three have not yet committed to changing actions. Four behaviour change processes played a significant role in raising awareness and forming the intention to quit among informants on the contemplation stage. Therefore, health students should not smoke to be a good agent of change for society. Behaviour change communication and health promotion need to ensure the involvement of the four change processes for smokers to be at the contemplation stage and readily moved to an action stage.